Resolution of the IV International Menopause Expert Forum - - (Publishing House TRILIST, 2023)
The IV International Menopause Expert Forum took place on November 24, 2022. The expert panel included leading endocrine gynaecologists from Armenia, Azerbaijan, Georgia, Kazakhstan, Moldova, Ukraine, Uzbekistan, and Ukraine. The experts discussed interdisciplinary cooperation in the management of menopausal women, the eligibility criteria for menopausal hormone therapy (MHT) and their implementation in routine clinical practice and developed an algorithm for switching from combined oral contraceptives (COCs) to MHT. Due to the lack of awareness and access to information and services related to menopause, interdisciplinary cooperation aimed at early detection of symptoms and diagnosis of menopausal disorders for timely treatment is paramount. The Forum participants highlighted the need for a series of steps to ensure comprehensive management of menopausal women. The Expert Forum reviewed the 2022 «Eligibility criteria for menopausal hormone therapy: a position statement from a consortium of scientific societies for the use of MHT in women with medical conditions». The developed criteria for the acceptability of different MHT types for women with comorbidities is an essential step in expanding the possibilities for the use of MHT by physicians of various therapeutic areas. Moreover, the criteria help to identify populations for whom certain types of MHT are associated with risks. Importantly, the discussed eligibility criteria are not yet universally accepted. Therefore, in routine clinical practice, when deciding whether to prescribe a particular type of MHT, it is vital to take an individual approach and assess the benefit/risk balance, considering the patient's combination of comorbidities, medical history, as well as the strengths and components of combination MHT, particularly the gestational component. Perimenopausal women may need contraception, including COCs. In such circumstances, physicians are faced with such questions as the acceptability of prescribing or continuing to use COCs for menopausal women, as well as when and how to switch from COCs to MHT. Thus, the Forum developed an algorithm for switching from COCs to MHT.